Bioprocessing and chemical compositions of Malaysia palm sugar: A review / Nurul Izzati Medihi ... [et al.] - Medihi, Nurul Izzati; Tan, Eddie Ti Tjih; Ahamad Zabidi, Mardiana; Abdul Muttalib, Siti Azima (2021)
Palm sugars had been traditionally used as a sweetener for decades in Malaysia. Palm sugars are produced by heating the filtered palm sap until it becomes concentrated and the desired colour and aroma are obtained. Then, the concentrated sap will be moulded, cooled for about an hour, and lastly, it will be packed. Their popularity is increasing globally due to their natural properties, minimal processing steps, and health benefits. Palm sugars typically do not undergo any purification process or use any synthetic chemical in their production. Although they are suggested to be a better sweetener than refined cane sugar, a comprehensive review of their nutritional qualities and product characteristics is not widely covered. Hence, this paper review aimed to explicate the chemical compositions and functional properties of Malaysia palm sugars as a potentially nutritious alternative sweetener. This paper was carried out by reviewing previously published studies on chemical compositions and functional properties of palm sugars. The key finding from this review unveiled that the bioprocessing of palm sugar highly affected the characteristics of the finished product. The two important processes that occurred during the heating stage of palm sap are the Maillard reaction and caramelisation process. These two processes greatly influenced the colour, flavor, and aroma of palm sugars. Palm sugars are considered nutritious because they contain adequate moisture, ash, protein, and fat. The chemical compositions of palm sugar are also a result of the minimal chemical processing of palm sugar.